Nepal: sublime surrounds simple life - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 1998)
Report on trip to Nepal, environmental conservation, and human development, 1998. A trek in the Himalayas proves a stimulating mix of the sublime majesty of nature and the simple life of the Nepalis. They eke out a living, terracing steep slopes with manual labor. They seem backward; there is personal integrity in their weathered faces. Everest is an icon of this dialectic of majesty and poverty.
Keywords: Nepal; Nepali; nature; conservation; culture; Everest; Nepalese; Himalayas